Nanotechnology in Medical Diagnostics: Innovations in Chemical Analysis for Early Disease Detection - Ibrahim, Zain Al-Abidin Khaled; Razouki, Hussain Maitham; Ali, Khitam hassan abd; Abbas, Zainab Faleh Muhammad Redha; Enad, Saja Nabhan (American Journal of Biomedicine and Pharmacy, 2025)
Nanotechnology is revolutionizing the field of medical diagnostics by enabling earlier, faster, and more accurate disease detection through innovations in chemical analysis. Despite recent advancements, a significant knowledge gap remains in translating nanoscale analytical techniques into clinically viable, point-of-care diagnostics with high sensitivity and specificity. This article explores the integration of nanomaterials—including nanoparticles, quantum dots, and biosensors—into chemical analysis tools such as spectroscopy, chromatography, and microfluidic systems. A multidisciplinary methodology is used to assess these innovations across detection platforms, highlighting their enhanced signal amplification, real-time detection capabilities, and suitability for biomarker discovery. The implications of this work suggest that nanotechnology can significantly improve early diagnostic outcomes, especially for chronic and life-threatening diseases, though regulatory, standardization, and interdisciplinary challenges must be addressed to achieve full clinical adoption.